A STUDY ON THE CHARACTERIZATION OF DUSTFALL - ARSLAN, M; BOYBAY, M (Pergamon-Elsevier Science Ltd, 1990)
A study was conducted of the dustfall around Elazig cement plant in Turkey. The work concentrated, particularly, on the characterization of particles. The soluble, insoluble, ignitable and unignitable fractions of particles were determined. The composition of dust pollution and its variation with meteorologial parameters, location and seasons, and the chemical and mineralogical composition, and trace element contents of particles were also studied. The experimental work was carried out at seven sampling stations for 15 months. The average rate of dust deposition over the area was 36.37 g m-2 month-1. The rates of deposition for insoluble (in water) and ignitable (at 900.degree. C) particles are 26.95 and 8.51 g m-2 month-1, respectively. The equilibrium pH of solutions shows that the particles deposited are rather alkaline in character. During the warm season the mean pH value is 8.63, during the cold season it is 6.49. The reduction of pH may be caused by acidic oxides such as SO2 originating from combustion processes. Calcium, silicon, aluminum and iron are the main constituents of the particles. The general view of composition is similar to cement or its raw materials. The XRD analysis shows that crystalline compounds are calcite, quartz, albite, muscovite, chlorite, edenite, dicalcium silicate and, possibly, other cement compounds and hydration products. The ratios of heavy metals such as Pb, Mn, Ni and Co are significant. The maximum concentration of lead was found to be 3600 mg kg-1.